2004
DOI: 10.1023/b:aseb.0000014326.64934.50
|View full text |Cite
|
Sign up to set email alerts
|

Gender Nonconformity, Childhood Rejection, and Adult Attachment: A Study of Gay Men

Abstract: Several childhood factors are reported to be associated with a homosexual orientation in men, including gender nonconformity and rejection by parents and peers. The purpose of this study was to explore the associations between these childhood factors and attachment anxiety (the tendency to experience anxiety regarding potential loss and rejection in close relationships) and attachment avoidance (the tendency to avoid versus seek out closeness in relationships) in gay and bisexual men. A community sample of 191… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
107
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(117 citation statements)
references
References 52 publications
6
107
2
2
Order By: Relevance
“…Specifically, acceptance (vs. rejection) predicts low avoidance, whereas independence-encouragement (vs. overprotection) predicts low attachment anxiety. In LGB samples, Mohr and Fassinger (2003) and Landolt, Bartholomew, Saffrey, Oram, and Perlman (2004) have found associations between perceived parental care in childhood and adult attachment anxiety and avoidance. In addition, Mohr and Fassinger found that perceptions of parents' sensitive care were indirectly related to attachment dimensions via perceived parental support for sexual orientation.…”
Section: Adult Lgb Relationshipsmentioning
confidence: 99%
“…Specifically, acceptance (vs. rejection) predicts low avoidance, whereas independence-encouragement (vs. overprotection) predicts low attachment anxiety. In LGB samples, Mohr and Fassinger (2003) and Landolt, Bartholomew, Saffrey, Oram, and Perlman (2004) have found associations between perceived parental care in childhood and adult attachment anxiety and avoidance. In addition, Mohr and Fassinger found that perceptions of parents' sensitive care were indirectly related to attachment dimensions via perceived parental support for sexual orientation.…”
Section: Adult Lgb Relationshipsmentioning
confidence: 99%
“…1 These sex differences together constitute gender expression, and children who do not conform to the expression typical of their biological sex are termed "gender nonconforming." Childhood gender nonconformity has been associated with an array of childhood psychosocial stressors, including poorer relationships with parents, 2,3 peer rejection, 3,4 harassment, 5 and physical and verbal victimization. [5][6][7] Possibly as a consequence of elevated exposure to stressors, childhood gender nonconformity has also been associated with a lower sense of well-being in adolescence 8 and mental health problems in adulthood, including depression and anxiety symptoms, 2 distress, 9 body dissatisfaction, 10 attachment anxiety, 3 and suicidality.…”
mentioning
confidence: 99%
“…In the attempt to explain the negative mental health consequences arising from gay-related stress in US society, researchers are increasingly finding that boyhood gender nonconformity, especially others' negative reactions to these behaviors, stand out as good predictors of later mental health difficulties in the lives of gay men (D'Augelli, Grossman, & Starks, 2006;Fitzpatrick, Euton, Jones, & Schmidt, 2005;Josephson & Whiffen, 2007;Landolt, Bartholomew, Saffrey, Oram, & Perlman, 2004;Skidmore, Linsenmeier, & Bailey, 2006). While Glassgold does not directly discuss Felix's childhood gender-related behavior, she does suggest that his current mental health is influenced by socialization into a culture with strong expectations of gender role conformity as well as by his ongoing engagement in traditionally masculine work and hobbies.…”
Section: Potential Hazards Of Masculine Ideology On Developmentmentioning
confidence: 99%
“…In fact, peers and fathers seem to be most rejecting of boyhood gender nonconformity and rejection from these sources mediates the link between boyhood gender nonconformity and later attachment difficulties and depressive symptoms among gay men (Josephson & Whiffen, 2007; Landolt, Bartholomew, Saffrey, Oram, & Perlman, 2004). Parental and peer rejection of childhood gender nonconforming behavior is associated with overall cognitive and interpersonal problems into adulthood (Josephson & Whiffen, 2007;Landolt, Bartholomew, Saffrey, Oram, & Perlman, 2004;Skidmore, Linsenmeier, & Bailey, 2006).…”
Section: Potential Hazards Of Masculine Ideology On Developmentmentioning
confidence: 99%
See 1 more Smart Citation